Sunday
March 26, 2017

Post a New Question

Posted by on .

Find the composition.

If f(x) = x^2 + 12 and g(x) = x^2 - 5, find (g*f)(x)

  • Math - ,

    f(x) = x^2 + 12 and g(x) = x^2 - 5, find (g*f)(x)

    g(f) = (x^2 + 12)^2 - 5
    = x^2 +24 x +144-5
    = x^2 + 24 x +139

  • Math - ,

    (g*f)(x) or (g○f)(x)
    =g(f(x))
    = g(x^2+12)
    = (x^2+12)^2 - 5
    = x^4 + 24x^2 + 139

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question